Structural Analysis of the Formal and Informal Jobs in the Brazilian Economy - Fernanda Sartori Camargo; Joaquim Jose Martins Guilhoto (European Regional Science Association (ERSA), 2006)
The reorganization of the Brazilian economy, in the globalization process, has brought out changes in its productive structure, and, consequently, changes in the job market. These changes had impact on the employment at the sectoral level, with great concerns related to the labor relations and to the growing unemployment rates. In the 1990s, the change in the focus of the development strategy, from a closed protected economy to an open economy with monetary control, has originated deep changes in the labor market. The number of employed persons in the primary and secondary sector was reduced, while in the tertiary sector there was an increase in the number of jobs, but not enough to absorb all the employees released from the previous two sectors. Besides the reduction in the capability of the economy to create new jobs, the last decade of the previous century has also showed an increase in the number of informal jobs. The share of informal jobs in the Brazilian economy was around 52% in 2003. In this way, the question of employment generated by the economic sectors, in number and quality, has become a crucial issue. The goal of this work is to study the characteristics and the evolution of the occupied persons, and to relate it with the formal and informal job market, as well as the economy productive structure, using for that input-output matrices constructed for the Brazilian economy. The main results show that there was a reduction in the capacity of the economy to generate employment for every million of Reais produced in a given sector. The data also shows that despite the ratio of informal workers in the economy being superior to the workers in the formality, the formal sector was responsible for about 60% of the jobs generated in the period of analysis.
Keywords: 330